Exploring the promising therapeutic benefits of iodine and radioiodine in breast cancer cell lines - Elliyanti, Aisyah; Hafizhah, Nurul; Salsabila, Dhianisa; Susilo, Veronica Y.; Setiyowati, Sri; Tofrizal, Alimuddin; Kurniawati, Yulia; Irrahmah, Miftah (Narra Sains Indonesia, 2024)
Iodine has an anti-proliferative effect on cancer cells; however, its effects have not been explored adequately. The aim of this study was to evaluate the therapeutic potential of iodine and radioiodine by assessing their effects on the viability of various breast cancer cell lines: MCF7, SKBR3, and MDA-MB231. The viability of cells was measured in treated cells exposed to six doses of iodine (5, 10, 20, 40, 60, 80 µM) and two doses of radioiodine (3.7×104 and 3.7×105 Bq). A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and modified clonogenic assays were used to assess cell viability. Exposure to 80 µM of iodine significantly reduced the viability of all cell types. The cells were then exposed to a 50% inhibitory concentration (IC50) dose. When the cells were exposed to the IC50 dose of iodine, the MCF7 cell viability was reduced by 42.6±0.14% (IC50 dose 12.88 µM), 40.2±0.08% for SKBR3 (IC50 dose 11.03 µM) and 47.0±0.02% for MDA-MB231 (IC50 dose 14.09 µM). All cells were also exposed to 3.7×104 Bq and 3.7×105 Bq radioiodine. Both doses significantly reduced the cell viability of MCF7 and SKBR3 cells compared to the unexposed control cells (all had p<0.05), while MDA-MB231 cell viability only reduced significantly after 3.7×105 Bq of radioiodine exposure compared to the unexposed control cells (p<0.05). This study highlighted that iodine had a toxic effect on breast cancer cells, and radioiodine enhanced the toxicity to breast cancer cells. The types of cancer cells and doses of iodine and radioiodine influenced the effect. These findings suggest that iodine and radioiodine hold promise as therapeutic agents for breast cancer, similar to their established use in thyroid disease treatment. However, further in vivo studies are important to provide more evidence.